2018
DOI: 10.1007/s00382-018-4135-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ENSO longitudinal position on teleconnections to the NAO

Abstract: While significant improvements have been made in understanding how the El Niño-Southern Oscillation (ENSO) impacts both North American and Asian climate, its relationship with the North Atlantic Oscillation (NAO) remains less clear. Observations indicate that ENSO exhibits a highly complex relationship with the NAO-associated atmospheric circulation. One critical contribution to this ambiguous ENSO/NAO relationship originates from ENSO's diversity in its spatial structure. In general, both eastern (EP) and cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 87 publications
(82 reference statements)
4
76
0
3
Order By: Relevance
“…Previous works have also shown that EP ENSO generates teleconnections with much stronger asymmetric features than those under CP ENSO (Frauen et al ., ; Feng et al ., ; Zhang et al ., ). In comparison to CP ENSO, the strong asymmetric impacts caused by EP ENSO are inherently unavoidable, because the preference location that EP ENSO often occurs is over the eastern Pacific, where the zonal climatological SST is characterized by strong asymmetry.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Previous works have also shown that EP ENSO generates teleconnections with much stronger asymmetric features than those under CP ENSO (Frauen et al ., ; Feng et al ., ; Zhang et al ., ). In comparison to CP ENSO, the strong asymmetric impacts caused by EP ENSO are inherently unavoidable, because the preference location that EP ENSO often occurs is over the eastern Pacific, where the zonal climatological SST is characterized by strong asymmetry.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Here the indices of Ren and Jin (2011) are used in correlation analysis because the EP and CP ENSO based on their indices can be better separated due to their low correlation. In addition, these previously mentioned indices could identify two types of El Niño but fail to distinguish different La Niña types (Zhang, Wang, Xiang, et al, 2015), including the indices of Ren and Jin (2011 1982, 1986, 1991, 1997, and 2015 (1994, 2002, 2004, and 2009), and the EP (CP) La Niña years are 1984, 1985, 1995, 1999, 2005, and 2007 (1983, 1988, 1998, 2000, 2008, 2010, and 2011). Please note that our qualitative conclusions remain the same if we use the other EP/CP index mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…During past decades, ENSO events have been divided into two different types: the central-Pacific (CP) and the eastern-Pacific (EP) El Niño/La Niña, with maximum positive/negative SST anomalies (SSTA) located in the central Pacific and the eastern equatorial Pacific, respectively (Ashok et al, 2007;Kao & Yu, 2009;Kug et al, 2009;Lee & McPhaden, 2010;Pan et al, 2018;Ren & Jin, 2011;Yu et al, 2011;Zhang, Wang, Xiang, et al, 2015, Zhang, Wang, Jin, et al, 2015. These two types of ENSO events are different in terms of their formation mechanisms and teleconnection signals (Ashok & Yamagata, 2009; and may induce different impacts on Z20 variability in the Indian Ocean, especially in the STIO region.…”
Section: 1029/2019gl082818mentioning
confidence: 99%
See 2 more Smart Citations